Skeletal maturation and growth rates are related to bone and growth plate injuries in adolescent athletics - Halvorsen Wik, E.; Martinez-Silván, D.; Farooq, A.; Cardinale, M.; Johnson, A.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Injuries are common in elite adolescent athletics, but few studies have addressed risk factors for injury. Growth and maturation are potential risk factors in this population; however, the current body of literature is both inconclusive and considered at high risk of bias. The aim of this study was therefore to examine if growth rate, maturity status and maturity tempo are associated with injury risk in an elite sports academy. Anthropometric, skeletal maturity and injury data collected prospectively over four seasons (117 athlete-seasons) were included in the analyses. Growth rate for stature was associated with greater risk of bone (Incidence rate ratio (IRR): 1.5 per one standard deviation increase above the mean; 95% CI: 1.1 to 1.9) and growth plate injuries (IRR: 2.1; 1.5 to 3.1). Growth rate for leg length was associated with greater overall injury risk (IRR: 1.3; 1.0 to 1.7) as well as the risk of bone (IRR: 1.4; 1.0 to 1.9) and growth plate injuries (IRR: 2.1; 1.4 to 3.0). Athletes with greater skeletal maturity, expressed as skeletal age (IRR: 0.6 per year; 0.5 to 0.9) and percentage of predicted mature height (IRR: 0.8 per percent increase; 0.7 to 1.0) were less prone to growth plate injuries. Rate of change in skeletal age was associated with an increased risk of bone injuries (IRR: 1.5; 1.0 to 2.3). The results of this study suggest that rapid growth in stature and leg length, skeletal maturity status and maturity tempo represent risk factors for certain injury types in adolescent athletics.